Modeling drug-induced liver injury and screening for anti-hepatofibrotic compounds using human PSC-derived organoids - Xiaoshan Wu; Dacheng Jiang; Yi Yang; Shuang Li; Qiurong Ding (Cell Regeneration, 2023)
Abstract Preclinical models that can accurately predict the toxicity and efficacy of candidate drugs to human liver tissue are in urgent need. Human liver organoid (HLO) derived from human pluripotent stem cells offers a possible solution. Herein, we generated HLOs, and demonstrated the utility of these HLOs in modeling a diversity of phenotypes associated with drug-induced liver injury (DILI), including steatosis, fibrosis, and immune responses. Phenotypic changes in HLOs after treatment with tool compounds such as acetaminophen, fialuridine, methotrexate, or TAK-875 showed high concordance with human clinical data in drug safety testings. Moreover, HLOs were able to model liver fibrogenesis induced by TGFβ or LPS treatment. We further devised a high-content analysis system, and established a high-throughput anti-fibrosis drug screening system using HLOs. SD208 and Imatinib were identified that can significantly suppress fibrogenesis induced by TGFβ, LPS, or methotrexate. Taken together, our studies demonstrated the potential applications of HLOs in drug safety testing and anti-fibrotic drug screening.